2008
DOI: 10.1038/nsmb.1397
|View full text |Cite
|
Sign up to set email alerts
|

ATAC is a double histone acetyltransferase complex that stimulates nucleosome sliding

Abstract: The Ada2a-containing (ATAC) complex is an essential Drosophila melanogaster histone acetyltransferase (HAT) complex that contains the transcriptional cofactors Gcn5 (KAT2), Ada3, Ada2a, Atac1 and Hcf. We have analyzed the complex by MudPIT (multidimensional protein identification technology) and found eight previously unidentified subunits. These include the WD40 repeat protein WDS, the PHD and HAT domain protein CG10414 (herein renamed Atac2/KAT14), the YEATS family member D12, the histone fold proteins CHRAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
202
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 183 publications
(212 citation statements)
references
References 58 publications
7
202
0
3
Order By: Relevance
“…Moreover, Herring and co-workers (48) reported that CHD8 interacted with SRF and modulated the function of SRF-dependent SMC-marker genes. Of interest, we report herein that WDR5 is contained within human ATAC2 histone acetyltransferase complexes, results consistent with two previous reports (34,35). However, the function of WDR5 within these complexes is unknown.…”
Section: Evidence That Wdr5 Mediates Chromatin Remodeling and Transcrsupporting
confidence: 80%
See 2 more Smart Citations
“…Moreover, Herring and co-workers (48) reported that CHD8 interacted with SRF and modulated the function of SRF-dependent SMC-marker genes. Of interest, we report herein that WDR5 is contained within human ATAC2 histone acetyltransferase complexes, results consistent with two previous reports (34,35). However, the function of WDR5 within these complexes is unknown.…”
Section: Evidence That Wdr5 Mediates Chromatin Remodeling and Transcrsupporting
confidence: 80%
“…Of interest, ATAC2 is the binding protein for CRP2 that has previously been shown to induce expression of multiple SMC-marker genes in fibroblast cells in combination with GATA4 and SRF (32,33). ATAC2 belongs to a histone acetyltransferase complex and has histone deacetylase activity by itself (34,35). Consistent with our findings, two different groups provided evidence that WDR5 is contained within the ATAC2 complex within several different cell types (34,35).…”
Section: Wdr5 Forms a Multiprotein Complex With H3k4 Hkmt Activity Ansupporting
confidence: 76%
See 1 more Smart Citation
“…The WDR5 protein is a subunit not only of the NSL complex but also of the MLL/SET1-containing histone H3K4 methyltransferase complexes (34) and of the ATAC (ADA2-containing) HAT complex, which includes as catalytic subunits both the GCN5/KAT2 and the ATAC2/KAT14 HATs (35,36). The degree to which the presence of these shared subunits argues for functional links between the NSL, INO80, ATAC, and MLL/SET1-containing histone H3K4 methyltransferase complexes remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some of these complexes also possess more than one activity. For example, the SAGA complex has both acetyltransferase (Gcn5) and deubiquitinase (Ubp8) activities (Ingvarsdottir et al 2005;Lee et al 2005), while the related ATAC complex possesses two acetyltransferases (Gcn5 and Atac2) (Suganuma et al 2008). Other complexes, such as TIP60, combine chromatin remodeling (H2A.Z incorporation by the p400 subunit) and modifying activities (acetylation by the Tip60 subunit) (Kusch et al 2004;Altaf et al 2009).…”
mentioning
confidence: 99%